УДОСКОНАЛЕННЯ АНАЛІТИЧНО-ПРОГНОСТИЧНИХ УМІНЬ МОЛОДОГО ВЧИТЕЛЯ ЗАСОБАМИ МЕТОДИЧНОЇ РОБОТИ ШКОЛИ (Педагогіка вищої та середньої школи, 2007)
The problem of forming of the analytic prognostic competence of yang specialists in the system of methodical work of school is considered in the article.